KEPEMIMPINAN KEPALA SEKOLAH PADA RINTISAN SEKOLAH BERTARAF INTERNASIONAL (Studi situs di SMP Negeri 1 Ungaran) - SUKOCO , BAGUS (2011)
There are two goals want to be reached in this research: 1) to know the characteristic of leadership of Principal of School at RSBI SMP Negeri 1 Ungaran. 2) to know the strategy that be used by the Principal in controlling the quality of school of RSBI SMP Negeri 1 Ungaran. The design of this research is descriptive research qualitative with approach of ethnography design. Research location is SMPN 1 Ungaran Kabupaten Semarang. The source of the data Used in this research are Principal, all teachers, employees and parents of the students and also document. The techniques of data collecting in this research are interview, observation and documentation study. The data analyse used int the research are reduced data, perform data; then conclusion and verification. The technique of the data analysed are 1) Trianggulasi 2) improving assidinity 3) using reference substance. The result of this research are; 1) the characteristic of leadership of the Principal use style ing ngarso sung tuladha, ing madya mangun karsa, tut wuri handayani. This style seems send SMP Negeri 1 Ungaran Succed in all achievement as well as make all staffs support all his policy so that be RSBI, 2) Quality Management Srategy use be principle Based School Management (MBS) Conducted by Principal of SMP Negeri 1 Ungaran together with teachers, employees, students and school committee that seriously want flexibility flexibility improvement in giving the facility of education and initiative in increasing the quality of management